Quality Active Charcoal from Skin Peanut Land (Arachis Hypogaea) with Various Activation Methods - Hermawan, Ujang; Sutanto, Sutanto; Kusumawardani, Linda Jati (Helium: Journal of Science and Applied Chemistry, 2024)
Peanut shells (Arachis Hypogaea) are characterized by seeds enveloped in sufficiently hard skin. The peanut shell is composed of organic compounds with the potential to be converted into activated carbon. This research aims to determine the quality of charcoal active with various activation methods and evaluated based on SNI 06-3730-1995. Chemical activation was conducted by immersion in 0.1 M NaOH, 0.1 M H2SO4, and 0.1 M NaCl, while physical activation was at a temperature of 500 ⁰C and without activation as a control variable. The best test results show by activating with a temperature of 500 ⁰C with results water content amounting to 3.58%, the results of here ash content were 3.82%, volatile matter of 9.55%, carbon content of 83.05%, benzene absorption capacity of 17.5177%, iodine absorption capacity of 753.23 mg/g. FTIR analysis shows that charcoal active with activation 500 ˚C contains C=O functional group, and SEM analysis showing the presence of varying pore surfaces in activated charcoal.